ANALISA PROSEDUR PENJUALAN SEPEDA MOTOR PADA PT MANDIRI MOTOR JAKARTA - roy irawan; Intan Kusuma Dewi; Darma Wijaya; Indra Prana (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
The ability to obtain profits can be obtained from sales. Sales will not go well without systematic and regular sales procedures. The system and rules in selling are called sales procedures. The purpose of this study was to find out how the procedure for selling motorbikes at PT Mandiri Motor in West Jakarta. In the data collection process, field research methods were carried out, namely observation and interviews as well as library research methods. The types of data used are primary data and secondary data. In data analysis techniques, the authors use descriptive analysis techniques. Based on the results of the analysis it can be concluded that the procedure for selling motorbikes at PT Mandiri Motor has sales procedures, namely sales planning, sales and payment processes and delivery